Semen parameters and male reproductive potential are not adversely affected after three or more months of recovery from COVID-19 disease - Stigliani, Sara; Massarotti, Claudia; Bovis, Francesca; Maccarini, Elena; Anserini, Paola; Scaruffi, Paola (Frontiers in Reproductive Health, 2023)
Background. The male reproductive system may be a potential target for SARS-CoV-2 since the presence of ACE and TMPRS2 receptors. After a first report of the presence of SARS-CoV-2 in semen of COVID-19 patients, several papers reported that SARS-CoV-2 was not detected in the semen. However, some evidences indicated that COVID-19 disease could impair semen parameters. During the infection, or in a short period after, a reduction in sperm concentration and motility and an increase in DNA fragmentation were observed, even in asymptomatic patients. There are no conclusive data exploring if this damage changes with time. We studied whether COVID-19 disease has a negative impact on semen parameters and male reproductive potential after recovery. Methods. In this longitudinal retrospective study, we enrolled 20 men who had COVID-19 disease. We compared sperm parameters in samples collected before COVID-19 and after infection (8.3 + 4.8 months). We also evaluated the reproductive potential in pre- and post-COVID-19 infertility treatments of 8 self-controlled couples as well as in 40 cycles after COVID-19 infection of the male partner. Results. For most patients, we obtained results of more than one semen analysis before and after COVID-19. After adjustment for age, days of sexual abstinence, frequency of ejaculations and presence of fever, we did not find significant difference over time in any semen parameter. The interval between COVID-19 infection and subsequent infertility treatments was 10.7 + 7.5 months. There were no differences in the embryological and clinical outcomes of infertility treatments performed before and after male infection. One couple obtained an ongoing single pregnancy in the post COVID-19 IUI. Normal fertilization (65%), cleavage (99%) and blastocyst development (40%) rates in treatments performed after male infection were within the expected range of competencies. A total of 5 singleton and 1 twin clinical pregnancies were obtained. To date, a healthy child was born, whereas 5 pregnancies are ongoing. A total of 10 blastocysts have been cryopreserved. Conclusion. Our data are reassuring that COVID-19 disease has no negative effect on semen quality and male reproductive potential when semen samples are collected three months or more after infection.